Interpersonal capitalization moderates the associations of chronic caregiving stress and depression with inflammation. (February 2020) - Gouin, J.P.; Wrosch, C.; McGrath, J.; Booij, L.
Highlights: Chronic stress and depression are associated with less interpersonal capitalization. Interpersonal capitalization is not associated with systemic inflammation in the full sample. Capitalization buffers the impact of chronic stress and depression on inflammation. Abstract: Chronic stress and depression can enhance chronic low-grade inflammation. Interpersonal factors may buffer the impact of stress and depression on inflammation. Interpersonal capitalization is a social support process in which one discloses positive personal events and experiences to close others. Greater capitalization may attenuate the deleterious impact of chronic stress and depression. The goal of the current study was to assess whether interpersonal capitalization is associated with inflammation and whether it moderates the association of chronic stress and depression with inflammation. In this cross-sectional study of chronic caregiving stress, 222 caregiving mothers of adolescents with developmental disabilities or comparison mothers of typically developing adolescents completed a self-reported daily diary assessment of capitalization, the Center for Epidemiological Study-Depression scale, and provided blood samples to assess interleukin-6, tumor necrosis factor-α, and C-reactive protein, three circulating inflammatory markers. Regression analysis indicated that there was no main effect of capitalization on inflammation, p = .24, R 2 = .006. However, there was a significant three-way interaction among capitalization, chronic caregiving stress, and depressive symptoms, p = .01, R 2 = .02. Among participants with lower capitalization, greater depressive symptoms were associated with higher inflammation in the caregiving group, but not in the comparison group. Among participants with higher capitalization, greater depressive symptoms were no longer significantly associated with higher inflammation among caregivers, but were marginally related to inflammation in the comparison group. Capitalization may thus be an interpersonal process mitigating the effects of chronic stress and depression on inflammation.